PERBANYAKAN SPORA ENDOMIKORIZA INDIGENUS PADA PERKEBUNAN KAKAO DENGAN PEMBERIAN MEDIA TANAM DAN KADAR AIR TANAH BERBEDA - Ni Kadek Trisnayanti; I Nyoman Rai; I Wayan Wiraatmaja (Plumula : Berkala Ilmiah Agroteknologi, 2021)
Cocoa is a plantation crop that has the potential to increase state income. In Bali, the highest cocoa production is in Jembrana Regency. Increasing the productivity of the cocoa plant can be achieve by using environmentally friendly fertilizer such as Arbuscular Mycorrhizal Fungi (AMF). The aim of this research is to obtain indigenous AMF isolates and their propagation with different planting media and water stress. The research was conducted from July to January 2021. Sampel AMF for islolation and identification was taken from Banjar Pangkung Medahan, Pulukan Village, Pekutatan District, Jembrana Regency, while isolation and identification of AMF was conducted at Agronomy and Horticulture Laboratory, Faculty of Agriculture, Udayana University, Laboratory of Plant Diseases, Laboratory of Genetic Resources and Molecular Biology of Udayana University and Greenhouse of Experimental Garden Faculty of Agriculture, Denpasar. This research used in propagating of spores of AMF was a Completely Randomized Design (CRD) with 2 factors and 4 replications. The first factor was planting medium which consisted of four treatment levels (soil planting medium, soil with sand growing media, soil with compost growing media, and sand with compost soil growing media) and the second factor was water stress which consisted of three treatment levels (ground water content of 100%, 70%, and 40% of field capacity). The results of isolation and identification showed that there were three genera of AMF spores found, i.e. Glomus, Gigaspora, Acaulospora. The results of spore propagation showed that soil and sand growing media with a combination of soil moisture content of 40% water field capacity produced the highest spores, which was 62 spores on average.